Shipping and Globalization in the Post-War Era Contexts, Companies, Connections - Petersson, Niels P.; Tenold, Stig; White, Nicholas J. (Palgrave Studies in Maritime Economics, 2019)
This open access book belongs to the Maritime Business and Economic History strand of the Palgrave Studies in Maritime Economics book series. This volume highlights the contribution of the shipping industry to the transformations in business and society of the postwar era. Shipping was both an example and an engine of globalization and structural change. In turn, the industry experienced and pioneered, mirrored and enabled key developments that led to the present-day globalized economy. Contributions address issues such as the macro-level shift of shipping's centre of gravity from Europe to Asia, the political and legal frameworks within which it developed, the strategies and performance of both successful and unsuccessful firms, and the links between the shipping industry and the wider economy and society. Without shipping and its ability to forge connections and networks of a global reach, the modern world would look very different. By bringing together scholars from various disciplinary and national backgrounds, this book advances our understanding of the linkages that bind economies and societies together.